FROM DEGRADATION TO RESILIENCE: LANDSCAPE-BASED ECOSYSTEM RESTORATION MODELS IN SOUTHEAST ASIA - Donny Juliandri Prihadi; Wayne Morgan; Patricia Taylor (Journal of Selvicoltura Asean, 2026)
Land degradation in Southeast Asia has become a critical environmental issue, exacerbating the impacts of climate change and threatening biodiversity, food security, and sustainable livelihoods. The rapid deforestation, soil erosion, and loss of ecosystem services have highlighted the need for effective landscape-based ecosystem restoration strategies. This study explores various models of ecosystem restoration aimed at transitioning from degraded landscapes to resilient ecosystems in Southeast Asia, emphasizing sustainable land management and community involvement. The research examines a range of restoration practices, from reforestation and agroforestry to soil rehabilitation and wetland restoration, assessing their effectiveness in restoring ecosystem functions and services. The study employs a mixed-method approach, combining qualitative case studies with quantitative data on biodiversity, carbon sequestration, and soil quality. The findings reveal that integrated landscape restoration approaches, which combine ecological, social, and economic considerations, yield the most significant improvements in ecosystem resilience. Additionally, the involvement of local communities and stakeholders in restoration activities enhances the sustainability of the projects. The research concludes that landscape-based ecosystem restoration is a viable strategy for combating environmental degradation and fostering resilience in Southeast Asia. It recommends the scaling up of these approaches to address larger areas affected by degradation, with an emphasis on long-term monitoring and adaptive management.